Evaluasi Implementasi Kurikulum Merdeka Dalam Pembelajaran Bahasa Arab Di Kelas X Man 2 Lamongan - Latifa, Siti Jamilatul; ., Winnuly; Fauziyah, Nina Rohmatul (Jurnal Murid, 2024)
Education has an important role in human life. In an education, it requires a curriculum. The curriculum in Indonesia continues to change, especially the curriculum in the realm of the Ministry of Education and Culture, which has now been agreed to become the Independent Curriculum. This affects school policies in implementing the learning process. Each school certainly has a different evaluation and is interesting to discuss. Therefore, the researcher tries to discuss how to implement the independent curriculum in learning Arabic at MAN 2 Lamongan, as well as find out the evaluation in the implementation. The objectives of this study are: 1) To find out the implementation of the independent curriculum in learning Arabic in class X MAN 2 Lamongan; 2) To find out the evaluation of the implementation of the independent curriculum in learning Arabic in class X MAN 2 Lamongan. This study uses a descriptive qualitative method with a case study approach. The subjects of this research are the Vice Chair of Curriculum, two Arabic teachers and MAN 2 Lamongan students. Data collection by conducting observations, interviews, and documentation. The results of this study state that: 1) The implementation of the Independent Curriculum at MAN 2 Lamongan was carried out for class X at the beginning of the new school year 2022 then in 2023 it will be continued gradually until now. The implementation is still gradual and according to the ability of each school, including planning, materials, implementation and evaluation. The existence of the Curriculum has a positive effect on learning Arabic, because students are trained to dare to communicate by actively discussing and moving forward. But sometimes there are also teachers who teach still using the k-13 curriculum method, because it adjusts the ability of students and the school environment. So, the method still uses lectures but the essence of the independent curriculum is focused on active sessions asking questions and the completeness of facilities and infrastructure for students ; 2) Evaluation of the implementation of the independent curriculum in class X MAN 2 Lamongan, namely researchers can identify by suggesting several actions such as Curriculum Adjustments, Changes in Teaching Methods, and Additional Training for Teachers. So, it is noted that the independent curriculum implemented at MAN 2 Lamongan has been running well but has not been fully maximized by covering several reasons as well as having an effect on the students such as, they are not satisfied with the results obtained when they finish learning or after the exam at the end of the semester.